Effectiveness of Sardine Consumption in Managing Dysmenorrhea and Anemia in Adolescent Girls - Mulyana, Hilman; Daryanti, Eneng (SAFE-Network, 2025)
Dysmenorrhea and anemia are common issues affecting adolescent girls, often requiring effective yet accessible non-pharmacological interventions. This study aimed to evaluate the effectiveness of omega-3 and iron (Fe) content in canned sardines in reducing menstrual pain and improving hemoglobin levels. A quasi-experimental design with a non-randomized pre-test and post-test control group was employed. The participants were 34 adolescent girls from SMK Bhakti Kencana Tasikmalaya experiencing dysmenorrhea, divided equally into intervention and control groups. Pain levels were measured using the Numeric Rating Scale (NRS), and hemoglobin levels were assessed using the Quick Check Set Hemoglobin Testing System. The intervention group consumed canned sardines for three consecutive days prior to the onset of dysmenorrhea, while the control group received conventional health education without any dietary intervention. The results showed no significant changes in pain or hemoglobin levels in the control group, while the intervention group demonstrated significant improvements in both outcomes. These findings suggest that the omega-3 and iron content in canned sardines is effective in reducing dysmenorrhea pain and increasing hemoglobin levels, thereby helping to prevent anemia in adolescent girls.